Investigating the effect of driven length and diameter of monopile on seismic performance of offshore wind turbines through Physical Modeling - A.R. Bateni; M. Moradi (مهندسی عمران شریف)
Global warming and its following environmental problems have led to increased attention to the use of renewable energy sources in most countries worldwide, and wind energy has emerged as a significant contributor. The use of wind energy through offshore wind turbines is one of the clean energy harvesting methods that initially began in Europe. Due to their larger size and higher wind speeds, offshore wind turbines have gained popularity worldwide, including seismic areas such as the United States and Southeast Asia, especially China. These turbines are located in marine environments and are subject to cyclic loads caused by wind, waves, and ocean currents. Monopiles, cylindrical hollow piles with diameters ranging from 2 to 8 meters and lengths of approximately 60 meters, are widely used to install offshore wind turbines. The design regulations for these turbines often overlook influential factors such as soil-structure interaction and refer to seismic design guidelines for onshore turbines. In this research, the seismic performance of monopiles has been investigated by conducting six experiments using a shaking table in a 1g condition. The effects of driven length and monopile diameter were analyzed, along with the impact of the installation medium being either saturated or dry. Various parameters, including ground motion acceleration, displacement, and induced excess pore water pressure, were scrutinized in this study. The results indicate that the saturated environment weakens their seismic performance. Therefore, the seismic design considerations for monopiles, based on the existing guidelines for dry structures, are inadequate. Furthermore, increasing the monopile diameter by 57% causes a 24% increase in the acceleration of the superstructure, a 40% increase in the cumulative displacement, and a 30% decrease in the average maximum displacement of the cycles during loading. It was also observed that by increasing or decreasing the driven length by about 15% compared to the driven length of the base monopile, the acceleration value of the superstructure increases by more than 20%, and the cumulative displacement value decreases by about 60%. The average maximum displacement of the cycles decreases by 30%, with an increase of 33% in the driven length.